The Ideological and Political Education in China's Universities Based on Big Data Thought - Cuiting, Wang (International Journal for Innovation Education and Research, 2015)
The rising up of big data idea has brought up a great influence and tremendous reformation in various fields in every country all around the world. Chances and challenges for the ideological and political education in China's universities are going hand in hand with the idea. Confronted with the new situation, a highlight should be cast onto the current situation of the ideological and political education in universities in big data era and the practical application of big data idea in the education so that mind-healthy, morality-lofty, highly educated and progressive high qualified talents in the era can be cultivated; and the ideological and political education in universities can remain active and vigorous.